Penerapan Model Berbasis Proyek untuk Mengembangkan Inovasi dan Estetika Mahasiswa di Mata Kuliah Kerajinan Jurusan PKK Universitas Negeri Medan - Saragih, Vina Gabriella; Daryana, Aditiya Pratama; Akita, Amalia (Universitas Syiah Kuala, 2025)
The Craft subject in the Culinary Education Study Program at Universitas Negeri Medan plays a crucial role in shaping students creativity, innovation, and aesthetic sensitivity. However, conventional teaching methods are often less effective in fostering active student engagement. This study aims to analyze the implementation of the Project-Based Learning (PjBL) model in the Craft course and its impact on the development of students innovation and aesthetics. This research employed a qualitative descriptive approach. Data were collected through classroom observation, in-depth interviews with two lecturers and six students, and documentation in the form of project reports and photos of students works. The learning process was conducted over one semester through stages of planning, implementation, evaluation, and reflection. The findings reveal that PjBL encouraged students to become more active, creative, and innovative. The projects produced, such as beaded tissue boxes, keychains, graduation flowers, and braided bags, demonstrated significant improvement in innovation and aesthetics. Challenges such as limited materials and time did not diminish the quality of the outcomes; instead, they motivated students to develop creative solutions. Overall, the application of PjBL proved effective in enhancing students collaborative skills, aesthetic abilities, and problem-solving capacities, making it a suitable method for sustainable implementation in Craft learning.